Hubungan Pembelajaran Pendidikan Agama Islam (PAI) Dengan Pemahaman Jiwa Keagamaan Siswa Di Bengkulu Selatan - Pasmah Chandra; Della Carolina (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2020)
Islamic religious education taught in schools is an important subject for students. Islamic Religious Education does not only cover cognitive sense in the form of knowledge and material, but more broadly covers the psychomotor domain and especially the affective domain which leads to the formation of student morals. Even Islamic Religious Education instilled in students must be able to form a strong understanding of the religious soul in students. Some previous studies have not touched on the level of understanding of the religious soul in students as a result of Islamic Religious Education. Previous studies only discussed the extent of Islamic Religious Education is relationship with the formation of students' character or character. The purpose of the research is to find out the relationship of Islamic Religious Education learning with the understanding of students' religious souls. The research method that I use is a type of quantitative research using the product moment formula and the data collection tools used in the form of observation, interviews, documentation and questionnaires. The sample in this study amounted to 36 people. Based on the results of research and calculations with an error level of 5% (trust) and N (36), then r table = 0.329. Then the price r count is greater than r table or 0.696> 0.329. Thus the results were obtained that H0 was rejected and Ha was accepted, meaning that there was a relationship between Islamic religious education learning and the understanding of the religious life of students of class sains in senior high school of 05 Bengkulu Selatan.